Determinant Factors of Consumer Attitude towards Online Shopping Mall - Pahlawan, Princhita Nabila Maram (International Journal of Economics, Business, and Entrepreneurship, 2021)
The number of Internet users recently increase due to the industrial revolution. This makes the change of consumers’ behavior, especially in buying the product through the online marketplace. The consumers’ behavior changes represent the attitude changes. Therefore, this research’s objective is to analyze determinants factors of the consumers’ attitude toward the online marketplace, known as e-commerce while the consumers buy the products, even though some of the e-commerce users or online shoppers still do not trust online shopping. They think there is a risk when they do online balance transactions. To answer the research objectives, this research uses quantitative design research and distributes questionnaires. The questionnaire was distributed to 350 target respondents through Google online. But, 315 usable data was analyzed through the SEM-Covariance model. SEM results show that shopper attitude towards Online Shopping Mall is most influenced by Perceived Benefit that is dominantly caused by Website Quality. While, online shoppers’ trust has a positive effect on attitude, influenced by eWOM. This makes a practical implication that the management of e-commerce must be aware of negative eWOM communications, in terms of the Website quality services. E-commerce management should improve the quality of its website services, especially in the design of attractive websites, and also maintain the trust of the consumers, such as increasing the security of financial transactions, providing credible information, and protecting the customers’ profile.